2014
DOI: 10.1371/journal.pone.0109357
|View full text |Cite
|
Sign up to set email alerts
|

Residency Patterns and Migration Dynamics of Adult Bull Sharks (Carcharhinus leucas) on the East Coast of Southern Africa

Abstract: Bull sharks (Carcharhinus leucas) are globally distributed top predators that play an important ecological role within coastal marine communities. However, little is known about the spatial and temporal scales of their habitat use and associated ecological role. In this study, we employed passive acoustic telemetry to investigate the residency patterns and migration dynamics of 18 adult bull sharks (195–283 cm total length) tagged in southern Mozambique for a period of between 10 and 22 months. The majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 46 publications
(66 reference statements)
9
90
3
Order By: Relevance
“…However, an absence of neonates in Sydney Harbor suggests this estuary was not functioning as an area for pupping, but could possibly be a location used for mating (Smoothey, unpublished data). This result differs from that of Daly et al (2014) who reported distinct temporal movements in adult C. leucas, presumed to be driven by seasonal temperature changes.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, an absence of neonates in Sydney Harbor suggests this estuary was not functioning as an area for pupping, but could possibly be a location used for mating (Smoothey, unpublished data). This result differs from that of Daly et al (2014) who reported distinct temporal movements in adult C. leucas, presumed to be driven by seasonal temperature changes.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent research has indicated segregation by size may occur in C. leucas populations with smallest individuals using river habitats and largest individuals inhabiting marine regions (Simpfendorfer et al, 2005;Brunnschweiler and Barnett, 2013). Movements and habitat use by juvenile bull sharks has been well-documented in several studies (Heupel and Simpfendorfer, 2008;Heithaus et al, 2009;Heupel et al, 2010;Curtis et al, 2013), but data on adult movements are limited (Daly et al, 2014). In one of the few explorations of adult movement satellite tagged C. leucas were tracked moving distances of 2-1506 km (mean 143.6 km) over periods up to 85 days in the Gulf of Mexico spending the majority of their time in warm, shallow coastal habitats (Carlson et al, 2010).…”
Section: Marine Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Even though there is no evidence that this species copulates in freshwater, parturition likely occurs in warm-water estuaries and rivers (Montoya, Thorson, 1982;Compagno et al, 2005;Pillans et al, 2006). Adult C. leucas sharks make use of shallow nearshore habitats (Brunnschweiler et al, 2010;Hammerschlag et al, 2012;Heupel et al, 2015;Graham et al, 2016), particularly in areas of high freshwater inflow, associated with an elevated productivity, where they usually exhibit some level of site fidelity (Carlson et al, 2010;Daly et al, 2014). Nevertheless, this species also undertakes coastal migrations regulated by environmental, foraging and reproductive drivers (Daly et al, 2014;Espinoza et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Adult C. leucas sharks make use of shallow nearshore habitats (Brunnschweiler et al, 2010;Hammerschlag et al, 2012;Heupel et al, 2015;Graham et al, 2016), particularly in areas of high freshwater inflow, associated with an elevated productivity, where they usually exhibit some level of site fidelity (Carlson et al, 2010;Daly et al, 2014). Nevertheless, this species also undertakes coastal migrations regulated by environmental, foraging and reproductive drivers (Daly et al, 2014;Espinoza et al, 2016). Open ocean migrations have also been observed, including one pregnant individual, which is known to have traversed the Indian Ocean from the Seychelles to Madagascar (Lea et al, 2015).…”
Section: Introductionmentioning
confidence: 99%